The Contribution of Biogeographic Ancestry and Socioeconomic Status to Racial/Ethnic Disparities in Type 2 Diabetes: Results from the Boston Area Community Health (BACH) Survey - Piccolo, Rebecca S. (2014)
PURPOSE: Racial/ethnic disparities in the incidence of type 2 diabetes (T2DM) are well documented and many researchers have proposed that biogeographical ancestry (BGA) may play a role in these disparities. However, studies examining the role of BGA on T2DM have produced mixed results to date. Therefore, the objective of this research is to quantify the contribution of BGA to racial/ethnic disparities in T2DM incidence controlling for the mediating influences of socioeconomic factors. METHODS: We analyzed data from the Boston Area Community Health (BACH) Survey, a prospective cohort with approximately equal numbers of Black, Hispanic, and White participants. We used Ancestry Informative Markers to calculate the percentages of West African and Native American ancestry of participants. We used logistic regression with g-computation to analyze the contribution of BGA and socioeconomic factors to racial/ethnic disparities in T2DM incidence. RESULTS: We found that socioeconomic factors accounted for 44.7% of the total effect of T2DM attributed to Black race and 54.9% of the effect attributed to Hispanic ethnicity. We found that BGA had almost no direct association with T2DM and was almost entirely mediated by self-identified race/ethnicity and socioeconomic factors. CONCLUSIONS: It is likely that non-genetic factors, specifically socioeconomic factors, account for much of the reported racial/ethnic disparities in T2DM incidence.